Climate change versus price stability: How "green" central bankers and members of the European parliament became pragmatic (yet precarious) bedfellows - Elsa C. Massoc (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
The European Central Bank (ECB) recently proclaimed a more active role for itself in the fight against climate change. Did the European Parliament (EP) play a part in this regard, and if so what was it? To answer this question, this paper builds on a multi-method text analysis of original datasets compiling communications between the ECB and the EP across three accountability forums between 2014 and 2021. The paper shows that there has been discursive convergence between central bankers and parliamentarians concerning the role of the ECB in combatting climate change. It argues that this convergence has resulted from a pragmatic (yet precarious) adoption of a common repertoire1 between 'green' central bankers and parliamentarians who have favored a more active role for the ECB in the fight against climate change. The adoption of a common repertoire is pragmatic, in that it results from the strategic use of specific discursive elements that are ambitious enough to address their respective opponents and trigger political change, yet vague enough to allow both sets of actors to converge on them momentarily. It is also precarious in the sense that it involves discarding fundamental political tensions, which is hardly tenable in the long term. The paper shows that both organizational and politicization dynamics have been at work in the emergence of this pragmatic yet precarious bedfellowship between 'green' central bankers and parliamentarians.
urn:nbn:de:hebis:30:3-651749
Keywords: 330; accountability; politicization; European Central Bank; European Parliament; climate; price stability